The Electronic Monitoring Paradigm: A Proposal for Transforming Criminal Justice in the USA - Stuart S. Yeh (Laws, 2015)
This article proposes a change in public policy that promises to greatly reduce major crime in the United States, protect society, eliminate prison overcrowding, and save taxpayer dollars. This policy would employ electronic monitoring (EM) technology in a way that discourages individuals who might otherwise be tempted to commit crimes. The approach is arguably more effective, efficient, humane and ethical than any alternative strategy and potentially could revolutionize law enforcement and the American criminal justice system.